Active monitoring of the state of motion in two-wheeled vehicles in absence of a valid GPS/GNSS signal. Issue 2 (2020) - Gelmini, Simone; Strada, Silvia; Tanelli, Mara; Savaresi, Sergio; Tommasi, Claudio De
Abstract: In insurance telematics, the information about the motion of a vehicle is mostly derived by a combination of inertial signals measured from e-Boxes installed integral to the vehicle. However, one must cope with poor reliability and possible lack of continuity of the GPS/GNNS signals. In this work, an inertial-based classification method that discriminates whether a two-wheeled vehicle is in motion is presented. This binary detection can be very helpful in circumstances where the GPS/GNNS signal is not sufficiently reliable and consequently the speed. With respect to what dead-reckoning algorithms do, the present contribution aims to recognize when the vehicle is moving without estimating the vehicle speed, but rather by correctly interpreting the intensity of the measured inertial signals. The approach has been extensively tested on experimental data, proving its suitability for practical applications.